Silica Nanowires Templated by Amyloid‐like Fibrils. Issue 45 (5th October 2015) - Al‐Garawi, Zahraa S.; Thorpe, Julian R.; Serpell, Louise C.
Abstract: Many peptides self‐assemble to form amyloid fibrils. We previously explored the sequence propensity to form amyloid using variants of a designed peptide with sequence KFFEAAAKKFFE. These variant peptides form highly stable amyloid fibrils with varied lateral assembly and are ideal to template further assembly of non‐proteinaceous material. Herein, we show that the fibrils formed by peptide variants can be coated with a layer of silica to produce silica nanowires using tetraethyl‐orthosilicate. The resulting nanowires were characterized using electron microscopy (TEM), X‐ray fiber diffraction, FTIR and cross‐section EM to reveal a nanostructure with peptidic core. Lysine residues play a role in templating the formation of silica on the fibril surface and, using this library of peptides, we have explored the contributions of lysine as well as arginine to silica templating, and find that sequence plays an important role in determining the physical nature and structure of the resulting nanowires. Abstract : Fibrillar peptide nanowire templates : Amyloid fibrils form silica nanowires with a peptidic core. By varying key residues within a known peptide sequence, lysine and arginine residues are shown to be necessary for templating the silica nanowire assembly.